Developing a vision strategic planning for the school librarian in the 21st century - Crowley, John D. (John Dennis) 1947- (Santa Barbara, Calif. Libraries Unlimited, 2011)
This text shows teacher librarians how to become leaders in their schools and apply their unique skills and insight to develop a timely and meaningful vision for the school's library.
Includes bibliographical references and index.
Keywords: School libraries -- Planning. -- United States; Instructional materials centers -- Planning. -- United States; High school libraries -- United States -- Case studies; Strategic planning